Hardware and software architecture for Plexil-based, simulation supported, robot automation - Cadavid Rengifo, Héctor Fabio; Chaparro Preciado, Javier Alberto (Bogotá. Colombia., 2016)
Some obsolete - but common - practices in the application of fertilizers and pesticides are causing serious environmental problems in Colombia; a situation that could be addressed by combining robotics and modern farming management principles, for example, the Precision Agriculture. This paper describes a novel application of Plexil - an experimental synchronous programming language developed by NASA-for robot automation in agriculture, supported by a simulation platform that allows quick prototyping of an automation plan, and a transparent integration of it on a physical robot. As a result, a methodology for evolutive robot development, and a case study with a real six-wheeled multipurpose agricultural robot are presented. Further applications of the simulation platform as a mean to easily introduce robotics engineers to alternative - and less error prone-programming models are also discussed.

Algunas prácticas obsoletas -pero comunes- en la aplicación de fertilizantes y pesticidas están causando serios problemas ambientales en Colombia; una situación que podría abordarse combinando la robótica y los principios modernos de gestión agrícola, por ejemplo, la agricultura de precisión. Este artículo describe una aplicación novedosa de Plexil, un lenguaje de programación síncrono experimental desarrollado por la NASA, para la automatización de robots en la agricultura, con el apoyo de una plataforma de simulación que permite la creación rápida de prototipos de un plan de automatización y una integración transparente del mismo en un robot físico. Como resultado, se presenta una metodología para el desarrollo de robots evolutivos y un caso de estudio con un robot agrícola multipropósito real de seis ruedas. También se analizan otras aplicaciones de la plataforma de simulación como un medio para introducir fácilmente a los ingenieros de robótica en modelos de programación alternativos y menos propensos a errores.
Keywords: agriculture; industrial robots; mobile robots; software architecture; Robots industriales; Arquitectura de software; Automatización; Sistemas de detección de robots; Robótica; Robot sensing systems; Automation; Actuators; Software; Adaptation models; Hardware